216k views
4 votes
Find dy/dx by implicit differentiation for ysin(y) = xcos(x)

1 Answer

6 votes

Answer:


(dy)/(dx)=(\cos(x)-x\sin(x))/(\sin(y)+y\cos(y))

Explanation:

So we have:


y\sin(y)=x\cos(x)

And we want to find dy/dx.

So, let's take the derivative of both sides with respect to x:


(d)/(dx)[y\sin(y)]=(d)/(dx)[x\cos(x)]

Let's do each side individually.

Left Side:

We have:


(d)/(dx)[y\sin(y)]

We can use the product rule:


(uv)'=u'v+uv'

So, our derivative is:


=(d)/(dx)[y]\sin(y)+y(d)/(dx)[\sin(y)]

We must implicitly differentiate for y. This gives us:


=(dy)/(dx)\sin(y)+y(d)/(dx)[\sin(y)]

For the sin(y), we need to use the chain rule:


u(v(x))'=u'(v(x))\cdot v'(x)

Our u(x) is sin(x) and our v(x) is y. So, u'(x) is cos(x) and v'(x) is dy/dx.

So, our derivative is:


=(dy)/(dx)\sin(y)+y(\cos(y)\cdot(dy)/(dx)})

Simplify:


=(dy)/(dx)\sin(y)+y\cos(y)\cdot(dy)/(dx)}

And we are done for the right.

Right Side:

We have:


(d)/(dx)[x\cos(x)]

This will be significantly easier since it's just x like normal.

Again, let's use the product rule:


=(d)/(dx)[x]\cos(x)+x(d)/(dx)[\cos(x)]

Differentiate:


=\cos(x)-x\sin(x)

So, our entire equation is:


=(dy)/(dx)\sin(y)+y\cos(y)\cdot(dy)/(dx)}=\cos(x)-x\sin(x)

To find our derivative, we need to solve for dy/dx. So, let's factor out a dy/dx from the left. This yields:


(dy)/(dx)(\sin(y)+y\cos(y))=\cos(x)-x\sin(x)

Finally, divide everything by the expression inside the parentheses to obtain our derivative:


(dy)/(dx)=(\cos(x)-x\sin(x))/(\sin(y)+y\cos(y))

And we're done!

User Wagner Patriota
by
4.6k points